2007
DOI: 10.1007/s10488-007-0122-2
|View full text |Cite
|
Sign up to set email alerts
|

Pediatrician Perspectives on Children’s Access to Mental Health Services: Consequences and Potential Solutions

Abstract: This paper examines pediatricians' perspectives regarding access to children's mental health care. In response to a question about factors that help or hinder coordination of care 190 respondents voluminously wrote about mental health access barriers. Responses were qualitatively analyzed to understand pediatricians' perspectives. Four thematic areas emerged: Insurance issues; availability of mental health specialty providers; state mental health systems; and pediatricians' attempts to improve access to mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Children’s mental health resources are lacking in comparison with the adult services in terms of collaboration with other professionals, 48 sometimes resulting in practitioners not being aware of services that may be available to their patients 56 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Children’s mental health resources are lacking in comparison with the adult services in terms of collaboration with other professionals, 48 sometimes resulting in practitioners not being aware of services that may be available to their patients 56 …”
Section: Resultsmentioning
confidence: 99%
“…A lack of providers of specialist services was the most highly endorsed barrier overall, with primary care practitioners expressing a clear desire for decreased waiting times and increased resources for referral, particularly in rural areas. 56 , 61 – 64 As all of the facilitators that were identified were the inverse of identified barriers, the discussion focuses on barriers from here on, unless explicitly stated otherwise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This included eight qualitative studies, six cross sectional studies, two studies using mixed methods, four audits of service data, and one case study. Long waiting times was the most commonly endorsed barriers cited by service users [37,45,48,50,53], healthcare professionals [54,55] and service managers [56]. In a study by McCann et al [48] adolescents reported long wait time for an initial appointment a major obstacle for getting MH support.…”
Section: Inflexible Servicesmentioning
confidence: 99%
“…More in-depth communication can also be supported through higher reimbursement for consultation. Providers have cited low reimbursement for consultation from Medicaid as a barrier to the delivery of high quality, patient-centered ADHD care (Pfefferle 2007). Empowering patients and their families to discuss their concerns, and providing support and follow-up over the long term could improve medication continuity, and contribute to the elimination of disparities.…”
Section: Clinical Significancementioning
confidence: 99%